Childhood Urinary Tract Infection: Clinical and Laboratory Profiles and Antimicrobial Sensitivity Patterns (Delta Medical College Journal, 2025)
Background: In infants and children, urinary tract infection (UTI) is a serious bacterial infection. Early detection and treatment can reduce the risk of substantial morbidity. Objective: The objective of the study was to evaluate the clinical profile, laboratory findings and antimicrobial sensitivity pattern of uropathogens causing urinary tract infection in children. Materials and method: This cross sectional study was conducted in the Department of Paediatrics Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, Bangladesh, from 1st January 2019 to 31st December 2019. A total of 150 cases aged 2 months to 12 years were enrolled in the study by consecutive sampling method. Results: Among 150 cases, 60% were female with a male-female ratio of 1:1.5. Overall, the highest number of cases were within the age group of 1 to